Civic Literacy for Sustainable Futures: Insights from a Systematic Review - Trimo Septiono; Afifah Hifzhillah; Anan Sutisna (Pedagogia: Jurnal Ilmiah Pendidikan, 2026)
This study aimed to systematically examine practices, strategies, and models for developing civic literacy across educational settings, digital environments, and public knowledge institutions in response to the growing challenges of misinformation, polarization, and digital transformation. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, including the stages of identification, screening, eligibility, and inclusion. A total of 30 peer-reviewed articles retrieved from national and international scholarly sources were analyzed using thematic analysis. The review explored six interrelated domains: civic learning, digital participation, educational policy, culture, libraries, and public knowledge spaces. The findings indicate that civic literacy is fostered through critical engagement with public information, dialogic and democratic communication, culturally responsive and local wisdom-based learning, and equitable access to reflective participation spaces within educational, digital, and public contexts. The synthesis further demonstrates that effective civic literacy initiatives integrate critical thinking, ethical reasoning, digital competencies, and participatory learning to strengthen informed citizenship. Civic literacy functions as a conceptual bridge between information literacy and Sustainable Development Goal (SDG) by enabling individuals to critically evaluate information, make ethical decisions, and participate responsibly in democratic life. These findings provide evidence-based implications for curriculum development, teacher education, and the design of inclusive democratic learning ecosystems across diverse educational contexts.